Antioxidant and anti-inflammatory effects of Turmeric and its impact on muscle damage induced by physical exercise: Is there a relationship? (Research, Society and Development, 2023)
Introduction: Muscle pain caused by intense physical exercise is characterized by discomfort and edema formation, especially when the body is not used to it, occurring due to microlesions of the muscle fibers, extending over a period of 24 to 72 hours. A food source of bioactive compounds with these activities is turmeric, which can be used in the prevention/recovery process of these injuries. Objective: To demonstrate the antioxidant and anti-inflammatory effects of turmeric and its impact on muscle damage induced by physical exercise. Methodology: A review research was carried out in Pubmed, Science Direct and SciELO databases. As inclusion criteria, original articles in English published between 2014 and 2020 were adopted. After initial filtering, a total of 916 articles were found, with 10 studies selected for the research. Results: 100% of the studies analyzed showed a positive effect of the use of turmeric in the attenuation of inflammatory and antioxidant markers, considering a variant dose of 90mg to 5g/day. Its ingestion also resulted in the reduction of pain perception in all studies. Longer duration protocols that performed post-exercise supplementation were more effective in reducing markers such as creatine kinase, interleukin-6, interleukin-8, interleukin-10, tumoral necrosis factor alpha, glutathione peroxidase and reduced glutathione. Conclusion: Based on the evidence found in the study, the effectiveness of using turmeric as a coadjuvant/strategy for the prevention and treatment of muscle pain caused by intense exercise can be verified.